Listening with Bamms: An Autotheoretical Critique of Epistemic Injustice in Postsecondary Early Childhood Education - Davies, Adam (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2026)
This article uses an autotheoretical approach to examine epistemic injustice in postsecondary early childhood education and care (ECEC). Drawing on Miranda Fricker’s framework of epistemic injustice and my personal narratives, I explore how dominant developmentalist and neoliberal discourses marginalize alternative knowledges and lived experiences in ECEC programs. Through reflective vignettes centered on affirmative experiences of being listened to by my grandmother, I analyze testimonial and hermeneutical injustices faced by educators and students whose identities and epistemologies fall outside of normative developmental frameworks. This article argues that hierarchical knowledge structures and accreditation standards perpetuate exclusion and proposes listening as an ethical and political practice to advance epistemic justice. It concludes by envisioning democratic ECEC spaces that embrace multiplicity, challenge developmentalist hegemony, and create openings for diverse ways of knowing and being.